2007
DOI: 10.1177/0310057x0703500410
|View full text |Cite
|
Sign up to set email alerts
|

In-Hospital Cardiac Arrest: Different Wards Show Different Survival Patterns

Abstract: The purpose of the study was to investigate the characteristics and outcomes of in-hospital cardiac arrests that occurred outside of the hospital critical care areas. A prospective register of adult in-hospital cardiac arrests occurring in non-critical care areas of Christchurch Hospital, Christchurch, New Zealand, from January 2001 to December 2004 was compiled. Two-hundred-and-forty-three cardiac arrests were recorded in this period. The overall return of spontaneous circulation was 38.7% (CI 32.6, 44.8) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 13 publications
3
11
0
Order By: Relevance
“…Survival was fourfold for patients with these rhythms compared with the rate for patients with non‐VT/VF rhythms. This is consistent throughout most studies of in‐hospital arrest 2,8,14,21,28,30,34,35,37–42 …”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…Survival was fourfold for patients with these rhythms compared with the rate for patients with non‐VT/VF rhythms. This is consistent throughout most studies of in‐hospital arrest 2,8,14,21,28,30,34,35,37–42 …”
Section: Discussionsupporting
confidence: 80%
“…We chose these times to reflect the level of senior medical staffing available in the location at the time of arrest 43 . Other authors have compared week days with weekends or divided days into 8 h blocks and found similar results 12,21,25,29,32,44,45 . We believe our definition more accurately reflects the clinical situation than a simple division based on time, especially as some areas have a more constant senior medical presence.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations